2001
DOI: 10.1207/s15327078in0202_9
|View full text |Cite
|
Sign up to set email alerts
|

Using Object Knowledge in Visual Tracking and Reaching

Abstract: Nine‐month‐old infants were presented with an engaging and challenging task of visually tracking and reaching for a rolling ball that disappeared and reappeared from behind an occluder. On some trials, the infant observed the experimenter place a barrier on the ball's track; the barrier remained partially visible above the occluder throughout the remainder of the trial. When the task involved only predictive tracking, infants' anticipatory gaze shifts were faster when no barrier was present. When the task invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 22 publications
4
56
2
Order By: Relevance
“…Berthier et al, 2001;Keen et al, 2003). In the present research, task demands were fairly minimal, and the infants revealed the same physical knowledge as in prior VOE tasks.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Berthier et al, 2001;Keen et al, 2003). In the present research, task demands were fairly minimal, and the infants revealed the same physical knowledge as in prior VOE tasks.…”
Section: Discussionsupporting
confidence: 48%
“…According to a third, processing-load account (e.g. Berthier et al, 2001;Boudreau & Bushnell, 2000;Keen, Carrico, Sylvia, & Berthier, 2003), infants fail to reveal their physical knowledge in an action task when the total processing demands of the task overwhelm their limited resources; processing demands depend on both (1) the complexity of the actions involved and (2) the complexity of the physical reasoning involved.…”
Section: Discrepancies Between Voe and Action Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Netelenbos, 2000). Although direct experimentation to test these alternative hypotheses has only started very recently (e.g., Berthier et al, 2001;Von Hofsten et al, 1998), a selective review of the literature suggests that in infancy vision for action and vision for perception are separate and develop independently. For instance, the study reported by Jouen, Lepecq, Gapenne, and Bertenthal (this issue) convincingly demonstrates that 3-day-old infants adjust their backward head movements to optic flow velocity.…”
Section: Action and Perception In Infancymentioning
confidence: 99%